Exploring the potentials of Sesuvium portulacastrum L. for edibility and bioremediation of saline soils - Zhang, Wenbin; Wang, Dan; Cao, Dingding; Chen, Jianjun; Wei, Xiangying (Frontiers in Plant Science, 2024)
Sesuvium portulacastrum L. is a flowering succulent halophyte in the ice plant family Aizoaceae. There are various ecotypes distributed in sandy coastlines and salty marshlands in tropical and subtropical regions with the common name of sea purslane. These plants are tolerant to salt, drought, and flooding stresses and have been used for the stabilization of sand dunes and the restoration of coastal areas. With the increased salinization of agricultural soils and the widespread pollution of toxic metals in the environment, as well as excessive nutrients in waterbodies, S. portulacastrum has been explored for the desalination of saline soils and the phytoremediation of metals from contaminated soils and nitrogen and phosphorus from eutrophic water. In addition, sea purslane has nutraceutical and pharmaceutical value. Tissue analysis indicates that many ecotypes are rich in carbohydrates, proteins, vitamins, and mineral nutrients. Native Americans in Florida eat it raw, pickled, or cooked. In the Philippines, it is known as atchara after being pickled. S. portulacastrum contains high levels of ecdysteroids, which possess antidiabetic, anticancer, and anti-inflammatory activities in mammals. In this review article, we present the botanical information, the physiological and molecular mechanisms underlying the tolerance of sea purslane to different stresses, its nutritional and pharmaceutical value, and the methods for its propagation and production in saline soils and waterbodies. Its adaptability to a wide range of stressful environments and its role in the production of valuable bioactive compounds suggest that S. portulacastrum can be produced in saline soils as a leafy vegetable and is a valuable genetic resource that can be used for the bioremediation of soil salinity and eutrophic water.